Causes of the Collapse of Household Foundations Interpretation Study - Saepudin, Asep (Journal of Islamicate Studies, 2022)
The household and family are the smallest social institutions of society that play a major role and influence social development and are the basis of a nation's life. The family has a role as the organizer of full human development through the implementation of its functions, namely: religious, socio-cultural, loving, protection, reproduction, socialization, education, economic, and environmental development. However, in fostering domestic life, there are sometimes disputes and divisions that lead to the collapse of household buildings. Therefore, several things that must be fulfilled by family members, especially between husband and wife, include regulating responsibilities in the implementation of each family member's obligations. Managing responsibilities between the two is very important to do so that domestic life becomes directed, tasks are organized, and the noble goals of the family are easy to achieve